Tolerance to frustration in six-year olds - Pavličević Slavica M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2012)
Tolerance to frustration is a psychological construct describing the behaviour of a person in a frustrating situation. It is defined as capability of a person to resist postponing or prevention of fulfillment of needs. This study is concerned with tolerance to frustration in six-year-olds, that is, in children nearing the end of preschool period. The investigation was conducted in a preschool institution Nata Veljković in Kruševac, on a sample of 114 children. The original research method involves the use of five stage Likert assessment scale. The assessors of the level of tolerance to frustration in children were care providers and parents. The findings of the investigation show that tolerance to frustration in six-year-olds is limited by their developmental and personality traits, as well as by certain conditions relating to child's development in family and preschool centre. The study confirmed the hypothesis that tolerance to frustration can serve as an indicator and a good predictor of emotional maturity of a child.